The Role of the State in Ensuring Workers’ Welfare According to the 1945 Constitution of the Republic of Indonesia - Sidiki, Efendi Gunawan (Ipso Jure, 2025)
Workers’ welfare constitutes an integral part of state objectives and constitutional rights as mandated by the 1945 Constitution of the Republic of Indonesia. However, constitutional norms governing the role of the state in ensuring workers’ welfare are formulated in general and declarative principles, resulting in normative ambiguity in their implementation. This ambiguity has led to inconsistencies in labor policies, a shift in the state’s orientation from welfare guarantor to labor market facilitator, and weakened legal certainty for workers in claiming their welfare rights. This study aims to analyze the role of the state in guaranteeing workers’ welfare under the 1945 Constitution and to examine the implications of constitutional normative ambiguity on labor policy and protection. The research employs a normative juridical method using statutory, conceptual, and case approaches. The findings indicate that normative ambiguity allows the reduction of state obligations in labor and social security policies, causing workers’ welfare to be compromised by economic efficiency considerations. Therefore, strengthening constitutional interpretation that affirms the state as the guarantor of workers’ welfare and harmonizing labor policies with the social justice values of the 1945 Constitution are essential.